Biosynthesis of ZnO nanoparticles using banana peel pectin for antibacterial and photocatalytic applications - Kazi Suraiya Islam; Md. Hasnain Mustak; Md. Khalid Hossain Shishir; Md. Minnatul Karim; Gazi Md. Arifuzzaman Khan (South African Journal of Chemical Engineering)
In this study, pectin was extracted from unripe banana peel utilizing a straightforward and unique sonochemical method. The extracted pectin was subsequently employed as an efficient ligand in synthesizing zinc oxide nanoparticles (p-ZnO NPs) through a green chemistry approach. The nanoparticles were characterized using X-ray diffraction (XRD), Scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy and UV–visible spectroscopy to evaluate their purity, size, morphology and crystallinity. The UV–vis analysis revealed absorption peak at 338.0 nm with an optical band gap of 3.08 eV, confirming the synthesis of p-ZnO NPs. The XRD analysis confirmed the formation of phase-pure wurtzite structures in the synthesized p-ZnO nanoparticles (NPs), with an average crystallite size of 28.78 nm. The SEM analysis revealed that the p-ZnO NPs exhibited rod-shaped morphology and the characteristic band observed in FTIR spectroscopy at 476 cm⁻¹. A potential mechanism for the formation of the p-ZnO NPs has been proposed. The photocatalytic activity of the p-ZnO NPs was assessed through the degradation of methylene blue (MB) dye under UV light. The maximum degradation efficiency of MB dye reached 78.5 % after 30.0 mins of UV light exposure. Moreover, the p-ZnO NPs exhibited a significant bactericidal effect against drug-resistant gram-positive Staphylococcus aureus but were ineffective against gram-negative Escherichia coli.